Qatar : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Qatar. (IMF Staff Country Reports; Country Report, 2008)
Budget revenue in FY2006/07 amounted to 42 percent of GDP, with hydrocarbon revenue mirroring rising oil prices. The current account recorded a surplus of about 31 percent of GDP in 2006. Monetary conditions were characterized by ample liquidity and strong credit growth. Qatar's medium-term (2008-12) outlook is favorable. As of June 2007, annualized inflation was estimated to have risen to 13 percent, compared with 12 percent during 2006. Designing a credible transition plan to implement the vision of a single financial market will be challenging.